Pengaruh Pemberian Infused Water Mentimun Terhadap Penurunan Tekanan Darah Pada Lansia Penderita Hipertensi di Wilayah Desa. Sindang jaya Kec.Cipanas Kab. Cianjur Tahun 2023 - Adinda Risti Sofyandi; Lannasari Lannasari; Siti Kamilah (Lembaga Pengembangan Kinerja Dosen, 2024)
As we get older,blood pressure will increase,causing the risk of hypertension. Hypertension is a degeneratif disease.Bload pressure that is left for a long time can cause damage to body organs such as stroke,coronary heart disease,which can cause death.Therefore,incereasing potassium intake is also one of the non- phamacological management of hypertension.This is done by consuming fruit and vegetables high in potassium,one of which is cucumber.There are several ways to cinsume cucumber.In this background,it is popular to use cucumber as Infused Water.The aim of this research for specifications,thare is an effect of giving infused water on reducing blood pressure in elderly people suffering from hypertension in the area of Desa SindangJaya Kec.Cipanas Kab,Cianjur.This research uses a quasi-experimental research design with a one group pretest-posttest design.The population in this study is all elderly people with hypertension in the SindangJaya village area.The sample for this research was taken using a purposive sampling technique and obtained a sample of using the Wilcoxon Signed Rank T-Test.There was a significant 2-tailed influene on the systolic and diastolic blood pressure of the respondents before administering cucumber infused water and after administering cucumber infused water,it was 0.000 < 0.005.There was a difference or effect of administering cucumber infused water on the systolic and diastolic blood pressure of respondents in the SindangJaya Village area,Cipanas district.Cianjur.There is an effect of giving cucumber infused water on reduccing blood pressure in elderly people suffering from hypertension in Sindangjaya village area,cipanas district,cianjur district in 2023.it s hoped that they wil be albe to continue on there awn by carrying out camplementry treatment by comsuming cucumber infused water so that blood pressure can remain normal.